Variety adoption and demand for quality seed in the central dry zone of Myanmar - Boughton, Duncan; Makhija, Simrin; Maredia, Mywish K.; Mather, David; Ortega, David L.; Spielman, David J. (Michigan State University, 2020)
For countries like Myanmar, where crop production accounts for the largest share of agricultural GDP, improved varieties are an essential source of increased and/or more stable crop yields. The adoption of improved varieties often increases the incentives for farmers to invest in complementary improved crop and soil management practices. For this reason most countries give priority to variety development, and Myanmar is no exception despite the very limited research budget allocated to crop research by the government. Yet improved varieties only generate benefits for farmers if they are adopted, and farmers only adopt new varieties if they are aware of their existence and benefits. For farmers to evaluate and adopt improved varieties they need access to quality seed (seed which is pure, exhibiting only the true genetic characteristics of the variety, with a high level of germination and uncontaminated by disease, weed seeds or other foreign matter). Access to quality seed is important because the attributes of farmer-saved seed degenerate with multiple seasons of use. Sustained benefits from variety adoption therefore require farmer awareness of, and access to, quality seed which preserves those benefits. Despite the importance of variety adoption and access to quality seed for crop productivity growth very few survey-based studies have been conducted in Myanmar. Our study focuses on the Dry Zone. This major agro-ecological zone was chosen for the following reasons. First, the Dry Zone is home to approximately 10 million people who are dependent directly or indirectly on farming for their incomes; second, a wide variety of crops are grown in the Dry Zone for which improved varieties have been officially released; third, access to improved varieties is recognized as an important means to adapt to rapid climate change experienced in the Dry Zone over the past thirty years (increased frequency of flooding and drought); and fourth, no previous survey-based studies on this topic have been undertaken for this zone. The specific objectives of the study are: 1) to determine the level of adoption of improved varieties for eight target crops; 2) to assess farmer preferences for varietal attributes for each of the crops; and 3) to assess the demand for quality seed. Data were collected using community and household surveys in 6 townships, two in each of the three regions that comprise the Dry Zone (Sagaing, Magwe and Mandalay Regions). Interviews were completed for a total of 1,388 households that produced at least one of the eight focus crops: rice, sesame, groundnut, pigeonpea, chickpea, green gram, black gram and sunflower. The results indicate that lack of awareness, not just lack of access, underlies low levels of uptake of improved varieties and quality seed by Dry Zone farmers. The good news is that this a problem that can be resolved through more intensive dissemination efforts, especially on-farm demonstrations that allow farmers to compare the performance of improved varieties or quality seed with their existing stock.